Social, economic & political thought. (New York, NY 3G E-LEARNING, 2019)
Provides an overview of the evolution of the political thought through different historical periods, giving an insight into the sociological and political conditions of the times that shaped the political.

This book offers an economical and useful approach to modern political thought.
Preface -- Chapter 1 The Fundamental Concept of Sociology -- Chapter 2 Social Thought -- Chapter 3 Economic Thought -- Chapter 4 Weber Economic Sociology -- Chapter 5 Right and Identity -- Chapter 6 Political Thought -- Chapter 7 Political Economy Growth -- Index.
Includes bibliographical references and index
Keywords: Political science -- Philosophy; Economics -- Philosophy